2012
DOI: 10.1021/la3022003
|View full text |Cite
|
Sign up to set email alerts
|

Control of Enzyme–Solid Interactions via Chemical Modification

Abstract: Electrostatic forces could contribute significantly toward enzyme−solid interactions, and controlling these charge−charge interactions while maintaining high affinity, benign adsorption of enzymes on solids is a challenge. Here, we demonstrate that chemical modification of the surface carboxyl groups of enzymes can be used to adjust the net charge of the enzyme and control binding affinities to solid surfaces. Negatively charged nanosolid, α-Zr(HPO 4 ) 2 •H 2 O (abbreviated as α-ZrP) and two negatively charged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…4,4751 Control of charge provided a strong handle to control interactions. Previously, 4 we have reported modification of GOx with TEPA where the net charge was flipped from net negative to net positive to trigger enzyme binding to anionic nanosheets. However, binding was examined with only one particular charge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,4751 Control of charge provided a strong handle to control interactions. Previously, 4 we have reported modification of GOx with TEPA where the net charge was flipped from net negative to net positive to trigger enzyme binding to anionic nanosheets. However, binding was examined with only one particular charge.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, the charge of glucose oxidase and hemoglobin has been flipped from negative to positive to enhance affinities with anionic nanosheets of α -ZrP by orders of magnitude, but increase in affinity as a function of systematic increase in enzyme charge has not been examined. 4 The design of rational methods to modulate enzyme binding to α -ZrP or other supports in order to enhance performance 20,21 and enzymatic activities is an unmet challenge. 22 Biocatalysis has been the basis of a broad range of applications including the production of amines 23 and synthesis of bionanomaterials, 24 and the use of α -ZrP as a nanosupport for such applications is promising.…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain strong electrostatic interactions, while maintaining the native conformation, the net charge of the protein can be engineered to control its binding affinities to a support surface. 200,201 One example reported by Kumar and co-workers 202 cationized negatively charged GOx and methemoglobin (Hb) by modifying their surface aspartate and glutamate side chains with tetraethylenepentamine (TEPA). The cationized proteins retained their secondary structure and activity to a significant extent and showed a 250-fold increase in affinity for the negatively charged support α-Zr(HPO4)2•2H2O.…”
Section: Immobilization Via Physical Adsorptionmentioning
confidence: 99%
“…To overcome them, in the past few decades, enzymes have been frequently immobilized on solid surfaces of physicochemically stable oxides or polymers (immobilized enzymes) to use them in chemical syntheses under non-biological conditions, 7,8 for example, asymmetric syntheses 9 and enzyme-based electrochemical sensors. [10][11][12] The immobilization improves not only enzymatic stability but also recyclability and reusability, because xation of tiny enzyme molecules to relative large supports can facilitate recovery from a reaction system by means of centrifugation, ltering and magnetic separation. Xie and co-workers have reported that lipases immobilized on iron based solid particles can be recycled by magnetic separation.…”
Section: Introductionmentioning
confidence: 99%